Crescimento de filmes finos de ni81fe19 para aplicações envolvendo magnetorresistência anisotrópica - Mori, Thiago José de Almeida (2011)
Anisotropic magnetoresistance (AMR) consists in the change of the resistivity of a ferromagnetic metal as a function of the angle between the current and the magnetization, what makes AMR-based sensors promising to measure both angular and linear positions. These devices usually have a structure of Ta/Ni81Fe19/Ta and the thickness of the Ni81Fe19 layer is about 10 nm so as to reduce the demagnetization field parallel to surface. In order to acquire high magnetic field sensitivity (S) and low Barkhausen noise the films should have high AMR values (ΔDR=R) and low coercivity. However, during fabrication, the structures are often exposed to temperatures above 200oC, what changes the characteristics of the interfaces and reduces ΔDR=R. On the other hand, ΔDR=R and S can be remarkably enhanced by insertion of nano-oxide layers that act like difusion barriers on the interfaces. The enhancement is mainly attributed to the large electron specular reflection at the flatter interfaces. In this work we have proposed to verify the possibility of enhance ΔDR=R and S in structures with good thermal stability just by adding an oxidation step after growthing each layer, forming TaOx. We studied the influence of the deposition parameters in the structural and magnetic properties of the samples and otimized the growth of thin films of Ni81Fe19 by magnetron sputtering. We also verified the influence of the annealing in the structural properties of nanostructures of Ta/Ni81Fe19/Ta exposed or not to oxidation on the interfaces. We observed that the TaOx nano-oxide layer can work as expected, however the poor cristalinity of the Ni81Fe19 layers leads to AMR values lower than the literature ones.